Attitude of Tourists in Understanding the Potential of Local Wisdom in Bukit Cinta Rawa Pening Tourist Attraction, Semarang Regency - Agnes Galih Chris Roseita; Esiria Lanus; Hanna Marbun; Mega Lumbantoruan; Sutarto Wijono (International Journal Labs, 2023)
Tourism is one of the sectors that play a role in the process of development and development of certain areas in terms of their existence which contributes to the income of the government and people in the tourist attraction area. The tourist attractions in this study focused on the Bukit Cinta Rawa Pening tourist attraction. Rawa Pening has located approximately 10 km from Ambarawa District and from several points along the Magelang-Semarang route, you can see the beauty of Rawa Pening. Rawa pening tourist attraction has the potential for local wisdom, namely the New Klinthing folklore that can attract tourists to visit. The potential of local wisdom can be maximized to make Rawa Pening if it is optimal can affect the attitude of tourists. Knowing and understanding the attitude of tourists can be done with evaluation actions such as the availability of criticism boxes and suggestions through direct interviews with tourists who come to Bukit Cinta Rawa Pening Tourism Object. Thus this research was carried out with the aim of knowing the attitude of tourists in understanding the potential of local wisdom in the Bukit Cinta Rawa Pening tourist attraction, Semarang Regency.The potential for local wisdom in the form of folklore is a special attraction for tourists who come. The research was conducted qualitative research methods with a descriptive approach. The results of the study explained that as many as 42.3% of respondents came to the Bukit Cinta Rawa Pening tourist attraction because of their attitude and interest in local wisdom of folklore which is full of values and norms of culture and historical science.